1995
DOI: 10.1002/bit.260480207
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and properties of carminomycin 4‐O‐methyltranferase, the enzyme which catalyzes the final step in the biosynthesis of daunorubicin in Streptomyces peucetius

Abstract: The carminomycin 4-O-methyltransferase enzyme from Streptomyces peucetius was covalently immobilized on 3M Emphaze ABI-activated beads. Optimal conditions of time, temperature, pH, ionic strength, enzyme, substrate (carminomycin), and cosubstrate (S-adenosyl-L-methionine) concentrations were defined for the immobilization reaction. Protein immobilization yield ranged from 52% to 60%. Including carminomycin during immobilization had a positive effect on the activity of the immobilized enzyme but a strongly nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…1; Table 3). Thus, the substrate specificity for DauK is much wider than was previously thought (8,9,31,41). With the expanded substrate range, we propose to rename this enzyme anthracycline 4-O-methyltransferase.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…1; Table 3). Thus, the substrate specificity for DauK is much wider than was previously thought (8,9,31,41). With the expanded substrate range, we propose to rename this enzyme anthracycline 4-O-methyltransferase.…”
Section: Resultsmentioning
confidence: 87%
“…The only previously proven reactions within this pathway were the 4-O-methylation of carminomycin and 13-dihydrocarminomycin to daunorubicin and 13-dihydrodaunorubicin, respectively (8,9,15,30,41), and the DoxA-catalyzed oxidation of daunorubicin to doxorubicin (14). The catalysts for all of the other reactions were either speculated, based on indirect evidence, or unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retamycin complex is a red powder with low solubility in water and high solubility in organic solvents (methanol, chloroform), and is produced as a secondary metabolite by submerged cultivations of Streptomyces olindensis . The isolation of new anthracyclins has been pursued in attempts to overcome its undesirable cardiotoxicity (Scotti and Hutchinson, 1995). Only a few studies have been published about this antibiotic, but retamycin showed promising results in the intercalation into DNA, which makes this antibiotic suitable to be used as a chemotherapy agent (Latorre, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In multi-covalent binding, the attachment points on the enzymes are relatively randomized, which implies lack of control on the position of enzyme structures. In some cases, covalent binding could induce unfavorable conformational changes in the protein structure, which could reduce enzymatic activity significantly (Jordao et al, 1996;Murtinho et al, 1998;Scotti and Hutchinson, 1995).…”
Section: Multi-point Covalent Binding 221mentioning
confidence: 99%